"The Right Kind of Children": Childhood, Gender and "Race" in Canadian Postwar Political Discourse - Helleiner, Jane (Anthropologica, 2022)
Located within newer anthropological writing on the cultural politics of childhood that is in part inspired by feminist work, this paper explores constructions of childhood in the parliamentary discourse of the immediate postwar period in Canada. Political debates from this period are located within a postwar political economy marked by an expanding welfare state, Cold war dynamics, and shifting understandings of both "race" and childhood itself. Federal parliamentary debates provide the material for an examination of how discourses of universalized as well as gendered and racialized childhoods emerged and were deployed in the project of nation-building.